1981
DOI: 10.1364/ao.20.000838
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-breakdown retropulse isolators for the infrared

Abstract: The design and performance of a passive plasma isolator for suppressing retropulses in high-power CO(2) laser-fusion systems are described. The device uses a gas-filled spatial filter designed to produce a plasma at the focal plane iris. General design criteria for these isolators are discussed, and the performance of a specific isolator is evaluated. For the unit tested, retropulse attenuations of 33 dB for focal plane intensities of 1.5 TW/cm(2) have been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The maximum C m obtained by using equation (15) Figure 4 where we have adequate value. The range over which this transition occurs is similar to that for IR fluence-limiting in 600 torr nitrogen (Figueira et al 1981), and in our thermal coupling measurements, as shown in table 3. For celluloid, taking the geometric mean between the table 2 predictions, we expected C m to decrease from a maximum value of 25 at / 0 = 3 x 10 7 W/cm 2 (/ 0 XVr = 17) during the transition from volume to surface absorption, to a value of about 1 at an orderof-magnitude higher intensity, I o = 3 x 10 8 W/cm 2 (/ 0 XVT = 170), taking ¥ « 1.…”
Section: Interaction Experiments Results and Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The maximum C m obtained by using equation (15) Figure 4 where we have adequate value. The range over which this transition occurs is similar to that for IR fluence-limiting in 600 torr nitrogen (Figueira et al 1981), and in our thermal coupling measurements, as shown in table 3. For celluloid, taking the geometric mean between the table 2 predictions, we expected C m to decrease from a maximum value of 25 at / 0 = 3 x 10 7 W/cm 2 (/ 0 XVr = 17) during the transition from volume to surface absorption, to a value of about 1 at an orderof-magnitude higher intensity, I o = 3 x 10 8 W/cm 2 (/ 0 XVT = 170), taking ¥ « 1.…”
Section: Interaction Experiments Results and Discussionsupporting
confidence: 85%
“…The films are an intimate mixture of Cr 2 O 3 and Cr crystallites, rather than discrete layers of the two constituents. Therefore, this structure well simulates the array of tiny, electrically insulated conducting spheres which has been predicted to exhibit extremely large, broadband absorptivity (Genzel & Kreibig 1980) for plasma reradiation and for the IR laser. The absorption coefficients are greater than 10 4 cm" 1 in the image of 0.4 to 10 /xm wavelength for Cr filling factors in the coating above 25%.…”
Section: Thermal/mechanical Coupling Measurements On Metalsmentioning
confidence: 84%
See 3 more Smart Citations